Spatial Analysis of The Suitability In Number of TPS at Kelurahan Based on Area And Number of DPT In DKI Jakarta Election 2017 - Nur Iman Santoso; Chotib Chotib (Publikasi Indonesia, 2024)
The number of TPS, in the 2017 DKI Jakarta Pilkada, was designed to suit the number of DPTs in one sub-district. There is a spatial relationship in the number of TPS, total DPT and the area between neighboring sub-districts which are processed using the Geoda application. The purpose of the study is Spatial Analysis of The Suitability In Number of TPS at Kelurahan Based on Area And Number of DPT In DKI Jakarta Election 2017. This research is based on data from the 2017 DKI Jakarta Regional Election Voters, which was conducted using quantitative research methods by describing the findings with the help of Geoda software. The results of the analysis on this conclusion show that the number of DPT and area area have a positive effect on the number of polling stations in Kelurahan in DKI Jakarta. In addition, there is a spatial relationship in the number of polling stations and the total DPT between neighboring villages.